Síndrome inflamatorio multisistémico y COVID-19: una revisión exploratoria - Eduardo Tuta-Quintero; Camila Martínez-Ayala; Gabriela Mantilla-Beltrán; Alejandro Rueda-Rodríguez; Juan Pimentel (Permanyer, 2022)
Background: Multisystem inflammatory syndrome temporally associated with COVID-19 presents with similar symptomatology and therapeutic approach to Kawasaki disease in the pediatric population. Given the novelty of the disease and the growing scientific literature on the subject, it is relevant to collect and report available scientific information. This review aimed to explore the medical evidence on multisystem inflammatory syndrome temporally associated with COVID-19 in a population under 18 years of age. Methods: We conducted a scoping review using Scopus and PubMed, including observational (cohort, case-control, and cross-sectional) studies and case series. Results: Of the total articles reviewed as of April 10, 2021, 45 articles met eligibility criteria: case series (n = 32), retrospective cohort studies (n = 6), prospective cohort studies (n = 4), case-control studies (n = 2), and cross-sectional studies (n = 1). Gastrointestinal and respiratory symptoms and myocardial dysfunction are the most commonly reported. The most relevant paraclinical markers were lymphopenia, thrombocytopenia, and elevated D-dimer levels. Conclusions: The multisystem inflammatory syndrome temporally associated with COVID-19 presents a broad spectrum of signs and symptoms. Aneurysms of the coronary arteries and myocarditis are usually present in the acute phases of the disease. The early diagnosis led by a multidisciplinary group of pediatric intensivists, infectious disease specialists, cardiologists, and rheumatologists allows adequate and effective medical management.